MEMBERSHIP IN THE EURASIAN ECONOMIC UNION OF KYRGYZSTAN (Third Sector Social Economic Review, 2019)
After the collapse of the Soviet Socialist Republics, new states emerged in the Eurasian region. Many of these states have applied to the process of regional integration. One of these integration processes is the Economic Union of Eurasia (EEU). This union has been established for economic purposes like the European Union. The idea of forming this union was first expressed in 1994 by the President of Kazakhstan Nursultan Nazarbaev. However, the fear of the USSR at that time prevented this idea from being passed on. EEU was founded in 2014. The aim is to ensure the economic well-being of the member countries. The effects of the EEU membership on the Kyrgyz economy were discussed in the study. Since joining the EEU (in the short term), the economy of Kyrgyzstan has been adversely affected. The reason for this is the economic inequality between the member states and the fact that the economy of Kyrgyzstan is not ready for this membership. Nonetheless, it is possible to say that the Kyrgyz economy will have positive long-term effects. Some of them are; the modernization of the Kyrgyzstan economy, the improvement of the conditions of the Kyrgyz migrants working in Russia, the opportunity to benefit from big markets and the reduction of customs controls.
Keywords: Eurasian Economic Union; Kyrgyzstan; Russia; Integration Process; Customs Union; Eurasian Economic Community.